Tinjauan Hukum Islam Kredit Online (Pay Later) dalam Transaksi Jual Beli Online Menurut Imam Madzhab - Barkah, Achmad Afad El; Auliya, Rizky Fitra; Aliyah, Nelud Darajaatul (AHKAM, 2024)
This study examines the compliance of online credit transactions, specifically the Pay Later feature, with Islamic law according to various Islamic jurists (Imam Madzhab). While many Muslims engage in business transactions, they often overlook Islamic principles, focusing on individual profits. The Pay Later system, which allows consumers to purchase items and defer payment, is scrutinized for its alignment with Islamic concepts such as Istijrar. Scholars argue that transactions where the total price is unknown until payment are impermissible. Although services like Shopee Pay Later meet several Islamic contractual criteria, they face criticism for potential riba (usury) due to additional charges. This research employs a descriptive qualitative approach, analyzing literature from books, journals, and Islamic texts, and concludes that while Pay Later transactions can meet Islamic requirements, their permissibility remains debated.